Strategi Public Relations Kitabisa.com Dalam Menjaga Reputasi Sebagai Donation Based Crowdfunding Platform - Dara Puspita (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
This study aims to examine the public relations strategies implemented by Kitabisa.com in maintaining its reputation as the largest donation-based crowdfunding platform in Indonesia. The research employs the PENCILS theory as the analytical framework, which includes seven elements: publication, event, news, community involvement, inform or image, lobbying and negotiation, and social responsibility. A qualitative descriptive approach was used, applying Miles and Huberman’s interactive analysis model. Data were collected through in-depth interviews with two internal representatives of Kitabisa.com and a public relations expert. The findings reveal that Kitabisa.com has actively implemented six out of the seven elements of the PENCILS strategy, with a strong emphasis on publication, community involvement, inform of image, and news as the main strengths in building and sustaining its reputation. However, the lobbying and negotiation aspect still requires improvement, particularly in establishing strategic relationships with government stakeholders. In conclusion, Kitabisa.com's public relations strategy has been effective in maintaining its institutional reputation, but strengthening advocacy efforts will be essential for ensuring long-term reputational resilience. ABSTRAK Penelitian ini bertujuan untuk mengetahui strategi public relations yang diterapkan oleh Kitabisa.com dalam mempertahankan reputasinya sebagai platform crowdfunding berbasis donasi terbesar di Indonesia. Kajian ini menggunakan teori PENCILS sebagai kerangka analisis strategi public relations, yang mencakup tujuh elemen: publication, event, news, community involvement, inform or image, lobbying and negotiation, dan social responsibility. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis interaktif dari Miles dan Huberman. Data diperoleh melalui wawancara mendalam dengan dua perwakilan internal Kitabisa.com dan seorang pakar humas. Hasil penelitian menunjukkan bahwa Kitabisa.com telah mengimplementasikan enam dari tujuh elemen strategi PENCILS secara aktif, dengan penekanan kuat pada aspek publication, community involvement, inform of image, dan news sebagai kekuatan utama dalam membangun dan menjaga reputasi. Namun, aspek lobbying and negotiation dinilai masih perlu ditingkatkan, khususnya dalam menjalin relasi strategis dengan pemangku kepentingan pemerintah. Kesimpulannya, strategi public relations Kitabisa.com secara umum telah berhasil menjaga reputasi institusi, namun penguatan pada elemen advokasi akan menjadi langkah penting untuk keberlanjutan reputasi di masa mendatang.